2011
DOI: 10.1002/anie.201105505
|View full text |Cite
|
Sign up to set email alerts
|

Implanting Nitrogen into Hydrocarbon Molecules through CH and CC Bond Cleavages: A Direct Approach to Tetrazoles

Abstract: From simple beginnings: A novel Cu‐promoted direct incorporation of nitrogen into simple hydrocarbon molecules under mild and neutral reaction conditions is described. 1,5‐Disubstituted tetrazoles are efficiently constructed by two C sp 3H and one CC bond cleavages (see scheme; TMS=trimethylsilyl). This protocol provides a new and unique strategy to functionalize simple and readily available hydrocarbon molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 129 publications
0
70
1
Order By: Relevance
“…(2)] . The produced open‐shell species may then react with the copper(I) catalyst [LCuI] + in a reductive fashion to produce the oxidized copper(II) complex 5 . This single electron transfer (SET) reaction should be feasible considering the inherent electrophilicity of the alkoxy radical and the reductive power of [LCu I ] + (for reference: E 1/2 Cu(II)/CuI in water is −0.093 V vs. SCE) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)] . The produced open‐shell species may then react with the copper(I) catalyst [LCuI] + in a reductive fashion to produce the oxidized copper(II) complex 5 . This single electron transfer (SET) reaction should be feasible considering the inherent electrophilicity of the alkoxy radical and the reductive power of [LCu I ] + (for reference: E 1/2 Cu(II)/CuI in water is −0.093 V vs. SCE) .…”
Section: Methodsmentioning
confidence: 99%
“…[30] Thep roduced open-shell species may then react with the copper(I) catalyst [LCuI] + in ar eductive fashion to produce the oxidized copper(II) complex 5. [31] This single electron transfer (SET) reaction should be feasible consideringt he inherente lectrophilicity of the alkoxy radical [32] and the reductivep ower of [LCu I ] + (for reference:E 1/2 Cu(II)/CuI in water is À0.093 Vv s. SCE). [33] Ta king into accountt he known propensity of copper(II) complexes to react with organic radicals, [27,34] the formation of the transient copper(III) intermediate 6 can be expected.…”
mentioning
confidence: 99%
“…Their importance in synthetic and medicinal chemistry has attracted considerable attention for the development of new synthetic strategies for these compounds. [12][13][14][15] Azides have been widely used in organic reactions, [16][17][18] but recent progress on the direct transformation of simple hydrocarbons into N-containing compounds [18] through a nitrogenation strategy encouraged us to try the direct transformation of alkynes. Although metal-catalyzed C C bond cleavage involving alkyne metathesis has been disclosed, [9,10] direct CC bond cleavage to form nitriles (Scheme 1 h) is still unknown and remains both challenging and of great value.…”
mentioning
confidence: 99%
“…In addition, it was shown that the diarylmethanes 5-349 , posesing elecron-rich aromatics, are also capable substrate for synthesis of tetrazoles 5-350 (Scheme 418). 674 …”
Section: Synthesis Of 5-membered Heterocycles With Two or More Hetmentioning
confidence: 99%